Editorial: Knowledge is Power, Ignorance is Bliss: Public perceptions and responses to human trafficking - Sharapov, Kiril; Hoff, Suzanne; Gerasimov, Borislav (Anti-Trafficking Review, 2019)
The focus of this issue of the Anti-Trafficking Review—public perceptions and responses to human trafficking—reflects the growing unease and disagreements among anti-trafficking practitioners and scholars about the current state of public awareness of human trafficking: how and by whom such awareness is produced and manipulated, whom it is targeting, and whether it leads, or can lead, to any meaningful anti-trafficking action. A central assumption in the anti-trafficking field is that the general public still lacks sufficient knowledge about human trafficking, and that creating more knowledge and awareness will lead to its reduction. However, there neither exists a common understanding of who should know what in order to achieve this goal, nor is there sufficient information available about the awareness of the general public or, especially, the impact of this awareness.